Facilitating or hindering learning - a meta-analysis of acceleration on video learning - Huang, Guan; Du, Yixuan; Yang, Hairu (Frontiers in Psychology, 2025)
IntroductionTime compression of instructional videos has received attention from scholars around the world. From existing empirical studies, a wide range of scholars have not yet reached a consensus on whether acceleration promotes video learning.MethodsThe article adopts a meta-analytic approach to analyze 12 domestic and international experimental and quasi-experimental research papers, exploring the role of moderating variables on the effect of acceleration on learning from the dimensions of teachers’ appearances, subtitles, and subject attributes.ResultsThe results of the study showed that the main effect test results found that accelerated playback of instructional videos increased learners’ cognitive load (g = 0.59) and decreased maintenance test scores (g = −0.41), migration test scores (g = −0.50), and learning satisfaction (g = −0.24). Moderation analyses revealed that teacher appearances played a moderating role in accelerating the effects of cognitive load and maintenance tests, and subtitles, country, and subject attributes played a moderating role in accelerating the effects of learning satisfaction.DiscussionTherefore, instructional video designers need to proactively consider the appropriate speed when developing instructional videos, and learners need to reasonably adjust the playback speed of the videos when learning from them in order to improve the quality of video teaching and learning. For educators, when designing teaching videos, they need to fully consider the impact of publication bias on the existing research results, and avoid blindly referring to the conclusions that may overestimate the effects of acceleration.